L-Cysteine-Derived H2S Promotes Microglia M2 Polarization via Activation of the AMPK Pathway in Hypoxia-Ischemic Neonatal Mice - Zhou, Xin; Chu, Xili; Xin, Danqing; Li, Tingting; Bai, Xuemei; Qiu, Jie; Yuan, Hongtao; Liu, Dexiang; Wang, Dachuan; Wang, Zhen (Frontiers in Molecular Neuroscience, 2019)
Our previous studies reported that L-Cysteine-derived H2S had remarkably neuroprotective effects against hypoxia-ischemic (HI) insult in neonatal animals. Here, we assessed one of the mechanisms of protection exerted by L-Cysteine which stimulate microglial polarization to the M2 phenotype and modulating complement expression after neonatal HI. L-Cysteine treatment suppressed the production of inflammatory markers, while dramatically up-regulated levels of anti-inflammatory cytokines in the damaged cortex. L-Cysteine administration promoted the conversion of microglia phenotype from inflammatory M1 to anti-inflammatory M2, associated with inhibiting p38 and/or JNK proinflammatory pathway and nuclear factor-κB activation. Furthermore, L-Cysteine decreased the HI-derived levels of complement proteins C1q, C3a and C3a receptor. Noting, blockade of H2S-producing clearly prevented L-Cysteine-mediated M2 polarization and complement expression. L-Cysteine significantly inhibited the neuronal apoptosis induced by the conditioned medium from activated M1 microglia in vitro. L-Cysteine treatment promoted AMPK activation and AMPK inhibitor abolished the anti-apoptotic and anti-inflammatory effects of L-Cysteine described above. Taken together, our findings suggested that L-Cysteine-derived H2S attenuated neuronal apoptosis after HI at least in part by enhancing microglia M2 polarization and modulating complement expression via AMPK activation.